A review of the inconsistency in CRM measurement: evidence from the telecommunication industry - Sarkindaji, Bashir Danlami; Abdullateef, Aliyu Olayemi; Hashim, Noor Azmi (American Research Institute for Policy Development, 2014)
This study explores the varying contradictions in CRM measurements and proposed a conceptual model in association with customer loyalty in the telecommunication industry.The model was developed based on observed practical issues, industry reports and explicit review of empirical literatures on CRM in multifaceted disciplines using qualitative technique.Findings from this research revealed an optimistic relationship between CRM measurements, customer satisfaction, switching costs and customer loyalty.Although few literature have established the influence of CRM measurements on customer loyalty effectiveness, this study has further availed scholars/practitioners knowledge of the theoretical ties and the role CRM maintenance as key measurement has in predicting successful CRM implementation. Furthermore, it is recommended that CRM implementing organizations integrate the need for CRM maintenance as a prerequisite for CRM sustainability in organizations.